Role of the lecturers in build culture environment pedagogy university - Nguyễn Quang Bình; Nguyễn Văn Minh (Tạp chí Nghiên cứu Khoa học Công đoàn, 2024)
The article focuses on clarifying the role of lecturers in building a university pedagogical cultural environment. This is a combination of material and spiritual cultural values created and enjoyed by members, in line with the school's pedagogical activities. On the basis of a conceptual assessment of the requirements for fundamental and comprehensive innovation in education and training, the author proposes a number of key measures to further promote the role of lecturers in building a pedagogical cultural environment of universities in the current period.